THE HOUR FULCRUM OF PIN DC NETWORK WITH HIGH RESISTANCE TO ELECTRIC CORROSION - Vasyliev, I. L.; Pavlychenko, M. Ye.; Pavlychenko, M. Ye. (Science and Transport Progress, 2008)
In UrGUPS a project of leg of the contact network support with a high resistance to electric corrosion is developed. New features are achieved through the protection of place of maximum mechanical load of the leg from flowing down currents in this zone by means of dielectric coating of some fixtures.